Toenail paronychia. Issue 4 (December 2016) - Lomax, Adam; Thornton, James; Singh, Dishan
Highlights: Paronychia is an infection in the lateral or proximal nail folds. The most common cause of paronychia is an ingrowing toenail. In the presence of paronychia, a causal ingrowing toenail should always be treated. Phenol ablation can be used to treat an ingrowing toenail even in the presence of infection. Chronic paronychia is usually non-infective and a dermatology opinion should be sought. Abstract: Paronychia is an inflammation of the tissues alongside the nail. It may be acute or chronic and can be seen in isolation or in association with an ingrowing toenail. Acute paronychial infections develop when a disruption occurs between the seal of the nail fold and the nail plate, providing a portal of entry for invading organisms. The treatment of paronychia associated with an ingrowing toenail is aimed at treating the causal toenail. In paronychia not associated with an ingrowing toenail, antibiotics may cure an early infection but surgical drainage of an abscess is often required. In this case, an intra-sulcal approach is preferable to a nail fold incision. Chronic paronychia is less common in the feet than in the hands. It is a form of contact dermatitis and is frequently non-infective, however the chronically irritated tissue may become secondarily colonised by fungi. A dermatology consultation should be obtained for suspected chronic paronychia. Patients with chronic paronychia that is unresponsive to standard treatment should be investigated for unusual causes, such as malignancy. An algorithm for the treatment of paronychia is presented in this review.